Transformasi Komoditas Perkebunan Adolina dari Tembakau ke Kelapa Sawit di Kecamatan Perbaungan, 1980-2020 - Angge Kurniawan; Laila Rohani (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2026)
This study examines the transformation of plantation commodities in Adolina, Perbaungan District, Serdang Bedagai Regency, from tobacco to oil palm between 1980 and 2020. The research is motivated by structural changes in the plantation economy of East Sumatra, a region historically recognized as a major producer of high-quality Deli tobacco. Driven by shifts in global market demand, rising production costs, and government policies promoting oil palm expansion, plantation land in Adolina gradually shifted from tobacco cultivation to oil palm estates. Employing the historical method with a qualitative approach through heuristics, source criticism, interpretation, and historiography, this study utilizes oral testimonies, archival records, plantation documents, statistical data, books, and scholarly journals. The findings reveal that the transition occurred progressively and was influenced by economic, social, agrarian, and policy-related factors. The conversion of plantation land altered labor structures from seasonal tobacco employment to more permanent oil palm labor arrangements and reshaped local economic patterns toward market-oriented livelihoods. The study argues that the transformation not only reflects economic adaptation but also contributes to the historiography of East Sumatran plantations by demonstrating the historical continuity and restructuring of agrarian relations in the post-colonial plantation sector.